Collagen-Based Hydrogel Encapsulated Cardiosphere-Derived Cell (CDC): Potential of Stem Cells as Tissue Repair Therapy Post-Acute Myocardial Infarction - Evananda, Maria Pramesthi Sabrina; Salim, Albert; Surya, Stevanus Christian; Suastika, Luh Olivia Saraswati (The Indonesian Heart Association, 2024)
Acute myocardial infarction (AMI) is a global health issue that is the leading cause of morbidity and mortality. Post-AMI management currently has therapeutic and side effect limitations, and has not been able to repair damage to myocardial tissue caused by AMI. The development and discovery of therapeutic modalities with the potential for a more optimal therapeutic effect remains a challenge in this post-AMI treatment. The purpose of this literature review is to collect and analyze various sources related to collagen-based hydrogel encapsulated cardiosphere-derived cell (CDC). This literature review is written systematically by gathering library sources from various search engines, such as Google Scholar, PubMed, and Research Gate. According to the findings of the study, CDC has the potential to be used as a post-AMI therapy because it can promote regeneration of the heart, which has lost function as a result of the AMI. To achieve the greatest effect, this modality is administered intracoronary. This modality will be encapsulated with collagen hydrogel, which has a cardioprotective effect, in order to increase the survival and effectiveness of CDC. The use of collagen-based hydrogel encapsulated CDC can provide post-AMI cell regeneration effects comparable to existing modalities while having minimal side effects. Further investigation in larger and more definitive trials is needed to elucidate the potential use of CDC therapy in AMI.